Applied Biomechanics: Sport Performance and Injury Prevention - Navarro, Enrique; Navandar, Archit; Veiga, Santiago; Juan Ferrer, Alejandro San (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue had, as its main objective, the compilation of biomechanical studies on sports performance and its relationship with musculoskeletal injuries. It is a collection of research on eight different sports (soccer, volleyball, swimming, cycling, skiing, golf, athletics, and hockey) considering injuries in general and specific injuries such as hamstring muscle injury, anterior cruciate ligament of the knee, and pain of the pubic symphysis. Additionally, it is noteworthy that most of the studies considered both men and women. Classical biomechanical tools have been used, such as 2D and 3D motion analysis, force platforms, and electromyography.